Healthcare utilisation and economic burden of cancer on Indian households - Md. Azharuddin Akhtar; Indrani Roy Chowdhury; Bhawna Taneja (Scientific Reports)
Abstract India is experiencing a rising incidence of cancer with a high mortality rate at a younger age. With high catastrophic healthcare expenditures and inadequate social security, it is imperative to investigate the health-seeking behaviour and corresponding economic burden on cancer-affected households. Using a nationally representative database, we use the matching methods to analyse healthcare utilization, healthcare expenditure, and financial distress of cancer-affected households. We find that the cancer-affected households report a longer hospital stay, more surgery, medicine uptake, and diagnostic tests per member compared to non-cancer households. The out-of-pocket healthcare expenditure borne by the affected households are significantly higher and mostly inflated through inpatient care. Further, we find some adverse spill-over effect in terms of lower per-member inpatient and outpatient visits and lower healthcare expenditure for non-cancer members of affected households when they are afflicted with any diseases. The catastrophic expenditures inflict income loss and distress financing to the cancer affected households. Further, we find per-member work force participation and non-medical consumption expenditures significantly low. We also observe heterogeneous effect in terms of lower inpatient visits, lower medicine uptake, lower capability to pay for treatment, and significantly higher borrowing and selling off assets among various cancer affected socioeconomically disadvantaged groups.